A Novel Dual-Targeted α-Helical Peptide With Potent Antifungal Activity Against Fluconazole-Resistant Candida albicans Clinical Isolates - Yang, Yang; Wang, Chenxi; Gao, Nan; Lyu, Yinfeng; Zhang, Licong; Zhang, Sujiang; Wang, Jiajun; Shan, Anshan (Frontiers in Microbiology, 2020)
Along with the expansion of the immunocompromised patient population over the past few decades, the incidence of fungal infections has markedly increased. Pathogenic fungi inevitably developed resistance to the clinically available antifungal agents, especially the most commonly used fluconazole, which poses a great challenge to clinical success and simulates the demand of novel antifungal agents. A promising alternative to the conventional agents is the use of antimicrobial peptide (AMPs). However, the antifungal activity of the AMPs is not fully developed. Therefore, this study attempted to design and screen α-helical peptides with potent antifungal activity, simultaneously, investigate the effect of key physicochemical parameters on antifungal activity. To serve this purpose, a series of lengthened and residue-substituted derivatives of the templated peptide KV, a hexapeptide truncated from the α-helical region of porcine myeloid antimicrobial peptide-36 (PMAP-36), were designed and synthesized. The enhancement of hydrophobicity by introducing aromatic hydrophobic amino acids (tryptophan and phenylalanine) significantly increased the efficacies of the peptides against all tested Candida albicans (C. albicans), including the fluconazole-resistant clinical C. albicans isolates. However, the toxicity of the peptide was also dramatically affected by increasing hydrophobicity. Among all designed peptides, RF3 with moderate hydrophobicity exhibited potent anticandidal activity (GM=6.96 μM) and modest hemolytic activity (HC10 >64 μM). Mechanistic studies revealed that RF3 exerted dual effects on C. albicans killing, namely, disrupting the membrane and inducing the production of ROS. Such dual targets (membrane and metabolism) of RF3 slow down the development of fungal resistance. In conclusion, these findings suggested that higher hydrophobicity was required to improve the antifungal activity of the AMPs and optimization of the hydrophobicity was necessary to improve the cell selectivity, which provide new insights into the design and development of antifungal peptides. Meanwhile, the successful design of RF3 highlights the potential utility of AMPs in preventing the spread of drug-resistant fungal infections.